2011
DOI: 10.1112/plms/pdr025
|View full text |Cite
|
Sign up to set email alerts
|

Spectral triples and characterization of aperiodic order

Abstract: We construct spectral triples for compact metric spaces (X, d). This provides us with a new metricds on X. We study its relation with the original metric d. When X is a subshift space, or a discrete tiling space, and d satisfies certain bounds we advocate that the property ofds and d to be Lipschitz equivalent is a characterization of high order. For episturmian subshifts, we prove thatds and d are Lipschitz equivalent if and only if the subshift is repulsive (or power free). For Sturmian subshifts this is equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(61 citation statements)
references
References 17 publications
1
60
0
Order By: Relevance
“…The main result of [39] showed that the spectral metric is Lipschitz equivalent to the underlying ultra metric if and only if the continued fraction entries of the slope of the Sturmian subshift are bounded, which in turn is equivalent to several known notions of aperiodic behaviour, as we will shortly explain in further detail. The typical choice of weightings used in [39] to define the spectral triple (in particular the Dirac operator) is suggested to be δ n = ln(n)n −t , where t > 0, and investigations of spectral metrics when δ n = n −1 have recently been carried out in [36]. Thus our choice of the weightings δ n = n −t , for t > 0, is a natural choice, generalising and extending this line of research.…”
Section: Introduction and Outlinementioning
confidence: 88%
See 3 more Smart Citations
“…The main result of [39] showed that the spectral metric is Lipschitz equivalent to the underlying ultra metric if and only if the continued fraction entries of the slope of the Sturmian subshift are bounded, which in turn is equivalent to several known notions of aperiodic behaviour, as we will shortly explain in further detail. The typical choice of weightings used in [39] to define the spectral triple (in particular the Dirac operator) is suggested to be δ n = ln(n)n −t , where t > 0, and investigations of spectral metrics when δ n = n −1 have recently been carried out in [36]. Thus our choice of the weightings δ n = n −t , for t > 0, is a natural choice, generalising and extending this line of research.…”
Section: Introduction and Outlinementioning
confidence: 88%
“…While spectral triples for cross product algebras of the form C(X) σ Z seem difficult to set up, see for instance [11,19,54] and references therein, there has been a lot of activity in constructing spectral triples for commutative C * -algebras C(Y ), where Y does not carry an obvious differential structure. A series of works has been devoted to general metric spaces [5,52,53,54] and specially to sets of a fractal nature [4,6,10,20,27,32,33,36,39,40,42,43,56]. Kellendonk and Savinien [39] proposed a modification of the spectral triple and spectral metric pioneered by Bellissard and Pearson [10], which in turn stems from the work of Connes [20] and Guido and Isola [32,33], that can be used to analysis Sturmians subshifts; this construction was later generalised to minimal subshifts over a finite alphabet in [38].…”
Section: Introduction and Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…However, in the special case of tiling algebras, this spectral triple essentially measured the Euclidean distance between two tilings in the groupoid used to define the C * -algebra, and ignored the substitution system. Since Bellissard and Pearson's seminal result there have been a number of papers on spectral triples of tilings, see for example [13,14,17,19]. The survey article [11] explains these constructions and their relationship to one another.…”
Section: Introductionmentioning
confidence: 99%